Quality of bone healing: Perspectives and assessment techniques. (May 2014) - Guda, Teja; Labella, Carl; Chan, Rodney; Hale, Robert
Abstract: Bone regeneration and healing is an area of extensive research providing an ever‐expanding set of not only therapeutic solutions for surgeons but also diagnostic tools. Multiple factors such as an ideal graft, the appropriate biochemical and mechanical wound environment, and viable cell populations are essential components in promoting healing. While bony tissue performs many functions, critical is mechanical strength, followed closely by structure. Many tools are available to evaluate bone quality in terms of quantity, structure, and strength; the purpose of this article is to identify the factors that can be evaluated and the advantages and disadvantages of each in assessing the quality of bone healing in both preclinical research and clinical settings.